THE INFLUENCE OF COMMUNICATION AND GENERATION DIFFERENCES ON THE PERFORMANCE OF EMPLOYEES AT INDONESIAN OIL PALM RESEARCH INSTITUTE IN MEDAN - Masyhuril Ahmad Prayogi; A. Rahim Matondang; Iskandarini; Yabani (CV. Radja Publika, 2024)
The purpose of this study was to examine the factors that influence employee performance at the Indonesian Oil Palm Research Institute as seen from Communication and Generational Differences. The sample selection used in this study was using the Slovin formula which resulted in 60 respondents. The data analysis technique used is multiple linear regression which consists of Classical Assumption Test (Normality Test, Multicollinearity Test, and Heteroscedasticity Test), Hypothesis Test (T Test and F Test), and Regression Coefficient Analysis. The results of this study indicate that: 1) communication affects employee performance, 2) generational differences have no effect on employee performance, 3) communication and generational differences simultaneously have a positive and significant effect on employee performance.